Adolescent and Young Adult Initiated Discussions of Advance Care Planning: Family Member, Friend and Health Care Provider Perspectives - Bedoya, Sima Z.; Fry, Abigail; Gordon, Mallorie L.; Lyon, Maureen E.; Thompkins, Jessica; Fasciano, Karen; Malinowski, Paige; Heath, Corey; Sender, Leonard; Zabokrtsky, Keri; Pao, Maryland; Wiener, Lori (Frontiers in Psychology, 2022)
Background and Aims: End-of-life (EoL) discussions can be difficult for seriously ill adolescents and young adults (AYAs). Researchers aimed to determine whether completing Voicing My CHOiCES (VMC) – a research-informed advance care planning (ACP) guide – increased communication with family, friends, or health care providers (HCPs), and to evaluate the experience of those with whom VMC was shared. Methods: Family, friends, or HCPs who the AYAs had shared their completed VMC with were administered structured interviews to assess their perception of the ACP discussion, changes in their relationship, conversation quality, and whether the discussion prompted changes in care. Open-ended responses underwent thematic analysis. Results: One-month post-completion, 65.1% of AYA had shared VMC completion with a family member, 22.6% with a friend, and 8.9% with an HCP. Among a sample of respondents, family (47%) and friends (33%) reported a positive change in their relationship with the AYA. Participant descriptions of the experience fell into 5 themes: positive experience (47%), difficult experience (44%), appreciated a guide to facilitate discussion (35%), provided relief (21%), and created worry/anxiety (9%). Only 1 HCP noted a treatment change. Family (76%), friends (67%), and HCP (50%) did not think the AYA would have discussed EoL preferences without completing VMC. Conclusions: VMC has potential to enhance communication about ACP between AYA and their family and friends, though less frequently with HCPs. Participants reported a positive change in their relationship with the AYA after discussing VMC, and described experiencing the conversation as favorable, even when also emotionally difficult.